Secondary battery and preparation method thereof
By using carbon and graphene-coated particles of the positive electrode of the energy storage battery cell, the battery cycle life and low temperature performance are improved, and the internal resistance and capacity of the traditional energy storage battery cell are solved. The problem of attenuation achieves longer battery life and higher energy density.
Patent Information
- Application Number
- CN202411607164.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-11-12
AI Technical Summary
After long-term cycles, the internal resistance of traditional energy storage batteries increases and capacity attenuates, resulting in a decrease in battery performance and service life, mainly due to the unreasonable design of the positive electrode material and structural design of the battery, especially the components of the electrode plate and lithium supplement agent. Improper selection of types leads to unstable voltage.
The active layer with a shell structure including carbon and graphene coated particles is lithium ferrate, lithium niobate and lithium niobate. By changing the structural design of the positive electrode sheet, the cycle life and low temperature performance of the battery are improved. Li+ is supplemented by lithium niobate to improve the release voltage and interface defects of lithium supplement agents.
It significantly improves the cycle life, low temperature performance and energy density of the energy storage battery cell, reduces internal resistance, extends the service life of the battery, and reduces the use of lithium supplements, solving the problem of low battery cycle life.
Smart Images

Figure CN119133420A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the photovoltaic field, and in particular to a secondary battery and a preparation method thereof. Background Art
[0002] With the continuous development of new energy technologies, energy storage cells, as key components, have been widely used in electric vehicles, energy storage systems and other fields. However, after long-term cyclic use, traditional energy storage cells often experience problems such as increased internal resistance and capacity attenuation, which seriously affects the performance and service life of the battery.
[0003] The problems of high internal resistance and low cycle life of batteries are mainly caused by the material and structural design of the battery positive electrode. Specifically, during the production of battery electrodes, the selection of electrode components and structures is unreasonable; the improper selection of lithium supplements leads to unstable voltage when the battery is using lithium supplements, affecting battery performance and cycle life.
[0004] The present application provides a secondary battery and a preparation method thereof, which solve the problem of low cycle life of the secondary battery. Summary of the invention
[0005] In order to solve the problem of low cycle life of secondary batteries, the present application provides a secondary battery and a preparation method thereof. The secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, the positive electrode sheet includes a current collector, an active layer is arranged on one or both sides of the current collector, the active layer includes a first active layer and a second active layer, the first active layer is arranged between the second active layer and the current collector, the first active layer includes carbon and graphene coated particles, the carbon and graphene coated particles are a shell-core structure consisting of a core and a shell layer surrounding the core, the material of the shell layer is carbon and graphene, the material of the core is one of lithium ferrite, lithium nickelate and lithium niobate, the shell layer is composed of a first shell layer close to the core and a second shell layer far away from the core compared to the first shell layer, the first shell layer is a carbon layer, the second shell layer is a graphene layer, and the material forming the carbon layer includes a mixed carbon source, and the mixed carbon source includes ethanol, ethylene, benzene, hexachlorobenzene and ethylene.
[0006] The materials of the first active layer and the second active layer are different. The positive electrode sheet of the present application can take into account the requirements of the energy storage cell for high specific energy and long cycle, and can simultaneously improve the cycle life, low temperature performance and energy density of the energy storage cell. The first active layer uses graphene to improve the internal resistance and low temperature performance of the battery; the carbon-coated particles reduce the internal resistance of the cell and improve the initial effect of the lithium supplement, reduce the use of the lithium supplement and maximize the capacity in the case of redundancy of the negative electrode; lithium niobate is used to supplement Li+ to improve the life of the battery. Compared with conventional lithium supplements, the lithium supplement has improved the problems of excessively high voltage, unstable air and too low amount of Li+ released, improved interface defects, and solved the problem of low cycle life of secondary batteries.
[0007] Optionally, the mass fraction of carbon and graphene-coated particles in the first active layer is 0.8% to 1.0%.
[0008] Optionally, the D50 particle size of the particles of the inner core is 5 μm to 10 μm, the thickness of the first shell layer is 60 nm to 100 nm, and the thickness of the second shell layer is 70 nm to 120 nm.
[0009] Optionally, the active layer includes lithium iron phosphate, the D50 particle size of the lithium iron phosphate is 0.6 μm to 1.6 μm, and the powder compaction density is ≥ 2.3 g / cm 3 , specific surface area 8m 2 / g~12m 2 / g.
[0010] Optionally, the thickness of the first active layer is 40 μm to 50 μm, and the thickness of the second active layer is 140 μm to 160 μm.
[0011] The present application also provides a method for preparing a secondary battery, which is used to prepare any of the secondary batteries described above, comprising: preparing carbon and graphene-coated particles using carbon, graphene and core materials; sequentially coating the carbon and graphene-coated particles and lithium iron phosphate on one or both sides of a positive electrode collector to obtain the positive electrode sheet; assembling the positive electrode sheet, negative electrode sheet, electrolyte and separator, and packaging them to obtain the secondary battery.
[0012] Optionally, the preparation method also includes: introducing an inert gas into a reaction vessel where the core material powder is placed, and after heating, adding a mixed carbon source to obtain a first coating material; cooling the first coating material, transferring it to a bag filter to obtain a second coating material; ultrasonically dispersing the second coating material in water to obtain a first dispersion, ultrasonically dispersing graphene in water to obtain a second dispersion, mixing the first dispersion and the second dispersion and dispersing them evenly by ultrasonic means to obtain a mixed dispersion; drying the mixed dispersion at 150°C, and heat treating it at 200°C to obtain the carbon and graphene coated particles.
[0013] Optionally, the preparation method further includes: placing the core material powder in a reaction container after pre-treatment, introducing an inert gas into the reaction container, heating the reaction container to 400°C to 800°C, adding a mixed carbon source and reacting for 0.2h to 3h to obtain a first coating material.
[0014] Optionally, the ratio of the carbon content of the mixed carbon source to the carbon content of the lithium iron phosphate in the active layer is 0.32-0.35:1.
[0015] Optionally, the mixed carbon source includes ethanol, ethylene, benzene, hexachlorobenzene and ethylene, and the mass ratio of ethanol, ethylene, benzene, hexachlorobenzene and ethylene in the mixed carbon source is 1:0.8~1.2:0.8~1.2:0.8~1.2:0.8~1.2.
[0016] Optionally, the method further includes: cooling the first coating material, and when the temperature is lower than 200° C., transferring the first coating material into a bag filter, and obtaining a second coating material by chemical vapor deposition.
[0017] The present application provides a secondary battery and a method for preparing the same. The secondary battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, the positive electrode comprises a current collector, an active layer is arranged on one or both sides of the current collector, the active layer comprises a first active layer and a second active layer, the first active layer is arranged between the second active layer and the current collector, the first active layer comprises carbon and graphene coated particles, the carbon and graphene coated particles are shell-core structures, the shell material is carbon and graphene, the core material is one of lithium ferrite, lithium nickelate and lithium niobate, the shell of the carbon and graphene coated particles is composed of two layers, the first shell close to the core is a carbon layer, and the second shell is a graphene layer. The cycle life is improved by changing the structure of the positive electrode sheet, and the problem of low cycle life of the secondary battery is solved. The present application also provides a method for preparing the above-mentioned secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the embodiments are briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.
[0019] Figure 1 A schematic diagram of the positive electrode structure provided for this application; Figure 2 A disassembled diagram of the secondary battery structure provided in an embodiment of the present application; Figure 3 This is a schematic diagram of the winding core structure in an embodiment of the present application.
[0020] Illustration Description: Among them, 1-aluminum foil; 2-first active layer; 3-second active layer. DETAILED DESCRIPTION
[0021] The following embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following embodiments do not represent all implementations consistent with the present application. They are only examples of systems and methods consistent with some aspects of the present application as detailed in the claims.
[0022] The problems of high internal resistance and low cycle life of secondary batteries are mainly caused by the material and structural design of the positive electrode of the battery. Specifically, during the production of the battery electrode, the selection of electrode components and structures is unreasonable; the type of lithium supplement is improperly selected, resulting in unstable voltage of the battery when using the lithium supplement, affecting the battery performance and cycle life, especially in extreme environments. The cycle life and energy density of the battery often cannot meet the needs of practical applications. This application achieves an increase in cycle life by changing the electrode structure.
[0023] The cycle life of a battery refers to the number of charge and discharge cycles that a battery can undergo under specified charge and discharge conditions. It is usually expressed in terms of the number of cycles. When the battery capacity drops to a certain percentage of the initial capacity (such as 80%), the battery is considered to have reached the end of its cycle life. The cycle life of a battery is affected by many factors, including the battery's charge and discharge rate, charge and discharge depth, temperature, and battery materials. A long cycle life means that the battery can maintain its stable performance for a longer period of time, thereby extending the service life of the equipment and reducing the cost of use. This is especially important for areas such as electric vehicles, energy storage systems, and equipment that needs to run for a long time. The cycle life of a battery is an important indicator for evaluating battery performance. A long cycle life can extend the service life of the equipment and reduce the cost of use.
[0024] In order to solve the problem of low cycle life of secondary batteries, the present application provides a secondary battery and a preparation method thereof. The secondary battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the positive electrode sheet comprises a current collector. An active layer is arranged on one or both sides of the current collector, and the active layer comprises a first active layer and a second active layer.
[0025] like Figure 1 As shown, the current collector is an aluminum foil 1, and an active layer is arranged on one side of the aluminum foil 1, and the active layer includes a first active layer 2 and a second active layer 3, and the first active layer 2 is arranged between the second active layer 3 and the aluminum foil 1; the first active layer 2 includes carbon and graphene-coated particles and lithium iron phosphate, and the second active layer 3 includes lithium iron phosphate.
[0026] The first active layer includes carbon and graphene coated particles, and the carbon and graphene coated particles are a core-shell structure consisting of a core and a shell surrounding the core, the shell is made of carbon and graphene, and the core is made of one of lithium ferrite, lithium nickelate and lithium niobate, the shell is composed of a first shell close to the core and a second shell farther away from the core than the first shell, the first shell is a carbon layer, and the second shell is a graphene layer, and the material forming the carbon layer includes a mixed carbon source, and the mixed carbon source includes ethanol, ethylene, benzene, hexachlorobenzene and ethylene.
[0027] It can be understood that the first active layer is composed of an inner core, a first shell layer surrounding the inner core, and a second shell layer surrounding the first shell layer, that is, a shell-core structure, the inner core is a lithium supplement material such as lithium ferrite, the first shell layer is a carbon layer, and the second shell layer is a graphene layer. Therefore, in this embodiment, the first active layer is defined to include carbon and graphene coated particles, and the carbon and graphene coated particles are the aforementioned shell-core structure. The materials of the first active layer and the second active layer are different. The positive electrode sheet of the present application can take into account the requirements of the energy storage cell for high specific energy and long cycle, and can simultaneously improve the cycle life, low temperature performance and energy density of the energy storage cell. The first active layer uses graphene to improve the internal resistance and low temperature performance of the battery; the carbon-coated particles (i.e., the first shell layer) reduce the internal resistance of the energy storage cell and improve the initial effect of the lithium supplement, reduce the use of the lithium supplement and maximize the capacity in the case of negative electrode redundancy; lithium niobate is used to supplement Li+ to improve the life of the energy storage cell. Compared with conventional lithium supplements, the lithium supplement has improved the problems of too high voltage, air instability, and too low amount of Li+ released, improved interface defects, and solved the problem of low cycle life of secondary batteries.
[0028] In some embodiments, the second active layer covers the entire surface of the first active layer.
[0029] In some embodiments, the mass fraction of carbon and graphene-coated particles in the first active layer is 0.8% to 1.0%. The mass fraction of carbon and graphene-coated particles in the first active layer refers to the percentage of the total mass of all core-shell structures in the first active layer to the mass of the first active layer.
[0030] In some embodiments, the mass fraction of carbon and graphene-coated particles in the first active layer is 0.9%.
[0031] In some embodiments, the D50 particle size of the particles of the inner core is 5 μm to 10 μm, the thickness of the first shell layer is 60 nm to 100 nm, and the thickness of the second shell layer is 70 nm to 120 nm.
[0032] In some embodiments, the D50 particle size of the particles of the inner core is 6 μm to 9 μm, the thickness of the first shell layer is 70 nm to 95 nm, and the thickness of the second shell layer is 75 nm to 105 nm.
[0033] In some embodiments, the D50 particle size of the core particles is 7 μm, the thickness of the first shell layer is 80 nm, and the thickness of the second shell layer is 100 nm.
[0034] In some embodiments, taking the total mass percentage content of the carbon and graphene-coated particles as 100 mol%, that is, the total mass percentage content of a single core-shell structure as 100 mol%, the mass fraction of the first shell layer is 1.2% to 1.4%, the mass fraction of the second shell layer is 0.8% to 1.0%, and the mass fraction of the core is 97.6% to 98%.
[0035] In some embodiments, taking the total mass percentage content of the carbon and graphene-coated particles as 100 mol%, that is, the total mass percentage content of a single core-shell structure as 100 mol%, the mass fraction of the first shell layer is 1.32% to 1.35%, the mass fraction of the second shell layer is 0.89% to 0.95%, and the mass fraction of the core is 97.7% to 97.9%.
[0036] In some embodiments, taking the total mass percentage content of the carbon and graphene-coated particles as 100 mol%, that is, the total mass percentage content of a single core-shell structure as 100 mol%, the mass fraction of the first shell layer is 1.34%, the mass fraction of the second shell layer is 0.9%, and the mass fraction of the core is 97.8%.
[0037] In some embodiments, the active layer includes lithium iron phosphate, the D50 particle size of the lithium iron phosphate is 0.6 μm to 1.6 μm, and the powder compaction density is ≥ 2.3 g / cm 3 , specific surface area 8m 2 / g~12m 2 / g.
[0038] Specifically, the first active layer may also include lithium iron phosphate; the second active layer may include lithium iron phosphate. The compacted density of the above powder is ≥ 2.3 g / cm 3 , specific surface area 8m 2 / g~12m 2 / g refers to the parameters satisfied by the lithium iron phosphate in the second active layer.
[0039] In some embodiments, the D50 particle size of the lithium iron phosphate is 0.7 μm to 1.5 μm.
[0040] In some embodiments, the D50 particle size of the lithium iron phosphate is 1.2 μm.
[0041] In some embodiments, the thickness of the first active layer is 40 μm to 50 μm, and the thickness of the second active layer is 140 μm to 160 μm.
[0042] In some embodiments, the thickness of the first active layer is 41 μm to 49 μm, and the thickness of the second active layer is 145 μm to 153 μm.
[0043] In some embodiments, the thickness of the first active layer is 47 μm, and the thickness of the second active layer is 147 μm.
[0044] The present application also provides a method for preparing a secondary battery, which can be used to prepare any of the above-mentioned secondary batteries, including: preparing carbon and graphene-coated particles using carbon, graphene and core materials; applying the carbon and graphene-coated particles and lithium iron phosphate on one or both sides of the positive electrode current collector in sequence to obtain the positive electrode sheet; assembling the positive electrode sheet, negative electrode sheet, electrolyte and separator, and packaging to obtain the secondary battery. It should be noted that the corresponding description in the above-mentioned secondary battery embodiment is also applicable to the embodiment of the secondary battery preparation method of the present application.
[0045] In some embodiments, the preparation method also includes: introducing an inert gas into a reaction vessel where the core material powder is placed, and after heating, adding a mixed carbon source to obtain a first coating material; cooling the first coating material, transferring it to a bag filter to obtain a second coating material; ultrasonically dispersing the second coating material in water to obtain a first dispersion, ultrasonically dispersing graphene in water to obtain a second dispersion, mixing the first dispersion and the second dispersion and dispersing them evenly by ultrasonic means to obtain a mixed dispersion; drying the mixed dispersion at 150°C, and heat treating it at 200°C to obtain the carbon and graphene coated particles.
[0046] In some embodiments, the preparation method further includes: placing the core material powder in a reaction container after pre-treatment, introducing an inert gas into the reaction container, heating the reaction container to 400°C~800°C, adding a mixed carbon source and reacting for 0.2h~3h to obtain a first coating material.
[0047] In some embodiments, the ratio of the carbon content of the mixed carbon source to the carbon content of the lithium iron phosphate in the active layer is 0.32-0.35:1.
[0048] In some embodiments, the mixed carbon source includes ethanol, ethylene, benzene, hexachlorobenzene and ethylene, and the mass ratio of ethanol, ethylene, benzene, hexachlorobenzene and ethylene in the mixed carbon source is 1:0.8~1.2:0.8~1.2:0.8~1.2:0.8~1.2.
[0049] In some embodiments, the method further includes: cooling the first coating material, and when the temperature is lower than 200° C., transferring the first coating material into a bag filter, and obtaining a second coating material by chemical vapor deposition.
[0050] In some embodiments, Figure 2 The secondary battery provided in the present application uses a square shell (aluminum shell) battery cell. The square shell (aluminum shell) battery cell has high mechanical strength, is conducive to mass production, has a high system grouping rate, can accommodate sufficient electrolyte, and is conducive to a long life.
[0051] In some embodiments, Figure 3 As shown, the positive electrode sheet, negative electrode sheet and separator provided in the present application are wound into a bare battery cell using a winding needle, and the alignment consistency of the positive electrode sheet and the negative electrode sheet is ensured by correction.
[0052] For ease of understanding, the following examples more specifically describe the contents disclosed in the present application, and these examples are only used for illustrative explanations, because it is obvious to those skilled in the art to make various modifications and changes within the scope of the present disclosure. Unless otherwise stated, all parts, percentages, and ratios mentioned in the following examples are based on weight.
[0053] Embodiment 1: After pre-treatment, lithium ferrite powder is placed in a reaction vessel, an inert gas is introduced into the reaction vessel, the temperature is raised to 400°C, and a mixed carbon source is added to react for 0.2h to obtain a first coating material. The mass ratio of ethanol, ethylene, benzene, hexachlorobenzene and ethylene in the mixed carbon source is 1:0.8.:1.2:0.8:0.8. The ratio of the carbon content of the mixed carbon source to the carbon content of lithium iron phosphate in the active layer is 0.32:1. The D50 particle size of the lithium ferrite particles is 10μm. The shell layer of the carbon and graphene coated particles consists of two layers, the first shell layer close to the core is a carbon layer, and the second shell layer is a graphene layer. The thickness of the first shell layer is 60nm, and the thickness of the second shell layer is 70nm. The first coating material is cooled, and when the temperature is lower than 200°C, the first coating material is transferred to a bag filter, and the second coating material is obtained by chemical vapor deposition.
[0054] The second coating material is ultrasonically dispersed in water to obtain a first dispersion, and the graphene is ultrasonically dispersed in water to obtain a second dispersion. The first dispersion and the second dispersion are mixed and uniformly dispersed by ultrasonic dispersion to obtain a mixed dispersion; the mixed dispersion is dried at 150° C. and heat-treated at 200° C. to obtain first carbon and graphene-coated particles. Taking the total mass percentage content of the first carbon and graphene-coated particles as 100 mol%, the mass fraction of the first shell layer is 1.2%, the mass fraction of the second shell layer is 0.8%, and the mass fraction of the core is 98%.
[0055] Active layers are provided on both sides of the positive electrode current collector to obtain the first positive electrode sheet. The thickness of the first active layer is 40μm, and the thickness of the second active layer is 140μm. Specifically, the first active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, PVDF as the binder, and the above-mentioned first carbon and graphene-coated particles as lithium supplements; and in the first active layer, the mass fraction of the positive electrode active material is 96.1%, the mass fraction of the conductive agent is 1.1%, the mass fraction of the binder is 2%, and the mass fraction of the lithium supplement is 0.8%. The second active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, and PVDF as the binder; and in the second active layer, the mass fraction of the positive electrode active material is 96.6%, the mass fraction of the conductive agent is 1.2%, and the mass fraction of the binder is 2.2%. The D50 particle size of the lithium iron phosphate in the active layer is 0.6μm, and the powder compaction density is 2.3g / cm 3 , specific surface area 8m 2 The first positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled and packaged to obtain the first secondary battery.
[0056] Embodiment 2: After pre-treatment, lithium nickelate powder is placed in a reaction vessel, an inert gas is introduced into the reaction vessel, the temperature is raised to 800°C, and a mixed carbon source is added to react for 3 hours to obtain a first coating material. The mass ratio of ethanol, ethylene, benzene, hexachlorobenzene and ethylene in the mixed carbon source is 1:1.2:0.8:1.2:1.2. The ratio of the carbon content of the mixed carbon source to the carbon content of lithium iron phosphate in the active layer is 0.35:1. The D50 particle size of lithium nickelate is 5μm. The shell layer of the carbon and graphene coated particles consists of two layers, the first shell layer close to the core is a carbon layer, and the second shell layer is a graphene layer. The thickness of the first shell layer is 100nm, and the thickness of the second shell layer is 120nm. The first coating material is cooled, and when the temperature is lower than 200°C, the first coating material is transferred to a bag filter, and the second coating material is obtained by chemical vapor deposition.
[0057] The second coating material is ultrasonically dispersed in water to obtain a first dispersion, and the graphene is ultrasonically dispersed in water to obtain a second dispersion. The first dispersion and the second dispersion are mixed and uniformly dispersed by ultrasonic dispersion to obtain a mixed dispersion; the mixed dispersion is dried at 150°C and heat-treated at 200°C to obtain second carbon and graphene-coated particles. The total mass percentage content of the second carbon and graphene-coated particles is 100 mol%, wherein the mass fraction of the first shell layer is 1.4%, the mass fraction of the second shell layer is 1%, and the mass fraction of the core is 97.6%.
[0058] Active layers are provided on both sides of the positive electrode current collector to obtain a second positive electrode sheet. The thickness of the first active layer is 50μm, and the thickness of the second active layer is 160μm. Specifically, the first active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, PVDF as the binder, and the above-mentioned second carbon and graphene-coated particles as lithium supplements; and in the first active layer, the mass fraction of the positive electrode active material is 95.9%, the mass fraction of the conductive agent is 1.1%, the mass fraction of the binder is 2%, and the mass fraction of the lithium supplement is 1.0%. The second active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, and PVDF as the binder; and in the second active layer, the mass fraction of the positive electrode active material is 96.6%, the mass fraction of the conductive agent is 1.2%, and the mass fraction of the binder is 2.2%. The D50 particle size of the lithium iron phosphate in the active layer is 1.6μm, and the powder compaction density is 2.5g / cm 3 , specific surface area 12m 2 The second positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled and packaged to obtain the second secondary battery.
[0059] Embodiment three: After pre-treatment, lithium niobate powder is placed in a reaction vessel, an inert gas is introduced into the reaction vessel, the temperature is raised to 500°C, and a mixed carbon source is added to react for 1 hour to obtain a first coating material. The mass ratio of ethanol, ethylene, benzene, hexachlorobenzene and ethylene in the mixed carbon source is 1:1.1:1.0:0.9:1.0. The ratio of the carbon content of the mixed carbon source to the carbon content of lithium iron phosphate in the active layer is 0.33:1. The D50 particle size of the lithium niobate particles is 7μm. The shell layer of the carbon and graphene coated particles consists of two layers, the first shell layer close to the core is a carbon layer, and the second shell layer is a graphene layer. The thickness of the first shell layer is 80nm, and the thickness of the second shell layer is 100nm. The first coating material is cooled, and when the temperature is lower than 200°C, the first coating material is transferred to a bag filter, and the second coating material is obtained by chemical vapor deposition.
[0060] The second coating material is ultrasonically dispersed in water to obtain a first dispersion, and the graphene is ultrasonically dispersed in water to obtain a second dispersion. The first dispersion and the second dispersion are mixed and uniformly dispersed by ultrasonic dispersion to obtain a mixed dispersion; the mixed dispersion is dried at 150°C and heat-treated at 200°C to obtain third carbon and graphene-coated particles. The total mass percentage content of the third carbon and graphene-coated particles is 100 mol%, wherein the mass fraction of the first shell layer is 1.3%, the mass fraction of the second shell layer is 0.9%, and the mass fraction of the core is 97.8%.
[0061] Active layers are provided on both sides of the positive electrode current collector to obtain a third positive electrode sheet. The thickness of the first active layer is 41μm, and the thickness of the second active layer is 145μm. Specifically, the first active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, PVDF as the binder, and the above-mentioned third carbon and graphene-coated particles as lithium supplements; and in the first active layer, the mass fraction of the positive electrode active material is 96%, the mass fraction of the conductive agent is 1.1%, the mass fraction of the binder is 2%, and the mass fraction of the lithium supplement is 0.9%. The second active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, and PVDF as the binder; and in the second active layer, the mass fraction of the positive electrode active material is 96.6%, the mass fraction of the conductive agent is 1.2%, and the mass fraction of the binder is 2.2%. The D50 particle size of the lithium iron phosphate in the active layer is 1.2μm, and the powder compaction density is 2.4g / cm 3 , specific surface area 10m 2 The third positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled and packaged to obtain the third secondary battery.
[0062] Embodiment 4: The fourth positive electrode sheet is obtained by setting an active layer only on one side of the positive electrode current collector. The thickness of the first active layer is 49μm, and the thickness of the second active layer is 153μm. Specifically, the first active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, PVDF as the binder, and the above-mentioned third carbon and graphene-coated particles as lithium supplements; and in the first active layer, the mass fraction of the positive electrode active material is 96%, the mass fraction of the conductive agent is 1.1%, the mass fraction of the binder is 2%, and the mass fraction of the lithium supplement is 0.9%. The second active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, and PVDF as the binder; and in the second active layer, the mass fraction of the positive electrode active material is 96.6%, the mass fraction of the conductive agent is 0.9%, and the mass fraction of the binder is 2.2%. The D50 particle size of the lithium iron phosphate in the active layer is 1.2μm, and the powder compaction density is 2.4g / cm 3 , specific surface area 10m2 The fourth positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled and packaged to obtain the fourth secondary battery.
[0063] Embodiment five: Active layers are provided on both sides of the positive electrode current collector to obtain the fifth positive electrode sheet. The thickness of the first active layer is 47μm, and the thickness of the second active layer is 147μm. Specifically, the first active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, PVDF as the binder, and the above-mentioned third carbon and graphene-coated particles as lithium supplements; and in the first active layer, the mass fraction of the positive electrode active material is 96.1%, the mass fraction of the conductive agent is 1.1%, the mass fraction of the binder is 2%, and the mass fraction of the lithium supplement is 0.8%. The second active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, and PVDF as the binder; and in the second active layer, the mass fraction of the positive electrode active material is 96.6%, the mass fraction of the conductive agent is 1.2%, and the mass fraction of the binder is 2.2%. The D50 particle size of the lithium iron phosphate in the active layer is 1.2μm, and the powder compaction density is 2.4g / cm 3 , specific surface area 10m 2 The fifth positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled and packaged to obtain the fifth secondary battery.
[0064] Embodiment six: Active layers are provided on both sides of the positive electrode current collector to obtain the sixth positive electrode sheet. The thickness of the first active layer is 45μm, and the thickness of the second active layer is 146μm. Specifically, the first active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, PVDF as the binder, and the above-mentioned third carbon and graphene-coated particles as lithium supplements; and in the first active layer, the mass fraction of the positive electrode active material is 95.9%, the mass fraction of the conductive agent is 1.1%, the mass fraction of the binder is 2%, and the mass fraction of the lithium supplement is 1.0%. The second active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, and PVDF as the binder; and in the second active layer, the mass fraction of the positive electrode active material is 96.6%, the mass fraction of the conductive agent is 1.2%, and the mass fraction of the binder is 2.2%. The D50 particle size of the lithium iron phosphate in the active layer is 1.2μm, and the powder compaction density is 2.4g / cm 3 , specific surface area 10m 2 The sixth positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled and packaged to obtain the sixth secondary battery.
[0065] Comparative Example 1: After pre-treatment, lithium niobate powder is placed in a reaction vessel, an inert gas is introduced into the reaction vessel, the temperature is raised to 850°C, and a mixed carbon source is added to react for 0.15h to obtain a first coating material. The mass ratio of ethanol, ethylene, benzene, hexachlorobenzene and ethylene in the mixed carbon source is 1:0.70.7:0.7:0.7. The ratio of the carbon content of the mixed carbon source to the carbon content of lithium iron phosphate in the active layer is 0.37:1. The D50 particle size of the lithium niobate powder is 9μm. The shell layer of the carbon and graphene coated particles consists of two layers, the first shell layer close to the core is a carbon layer, and the second shell layer is a graphene layer. The thickness of the first shell layer is 130nm, and the thickness of the second shell layer is 130nm. The first coating material is cooled, and when the temperature is lower than 200°C, the first coating material is transferred to a bag filter, and the second coating material is obtained by chemical vapor deposition.
[0066] The second coating material is ultrasonically dispersed in water to obtain a first dispersion, and the graphene is ultrasonically dispersed in water to obtain a second dispersion. The first dispersion and the second dispersion are mixed and uniformly dispersed by ultrasonic dispersion to obtain a mixed dispersion; the mixed dispersion is dried at 150°C and heat-treated at 200°C to obtain a first comparative carbon and graphene-coated particles. Taking the total mass percentage content of the first comparative carbon and graphene-coated particles as 100 mol%, the mass fraction of the first shell layer is 1.2%, the mass fraction of the second shell layer is 0.8%, and the mass fraction of the core is 98%.
[0067] Active layers are provided on both sides of the positive electrode current collector to obtain a first comparative positive electrode sheet. The thickness of the first active layer is 42μm, and the thickness of the second active layer is 140μm. Specifically, the first active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, PVDF as the binder, and the above-mentioned first comparative carbon and graphene-coated particles as lithium supplements; and in the first active layer, the mass fraction of the positive electrode active material is 96.3%, the mass fraction of the conductive agent is 1.1%, the mass fraction of the binder is 2%, and the mass fraction of the lithium supplement is 0.6%. The second active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, and PVDF as the binder; and in the second active layer, the mass fraction of the positive electrode active material is 96.6%, the mass fraction of the conductive agent is 1.2%, and the mass fraction of the binder is 2.2%. The D50 particle size of the lithium iron phosphate in the active layer is 1.7μm, and the powder compaction density is 2.0g / cm 3 , specific surface area 13m 2 The first comparative positive electrode sheet, negative electrode sheet, electrolyte and separator were assembled and packaged to obtain the first comparative secondary battery.
[0068] Comparative Example 2: After pretreatment, lithium niobate powder is placed in a reaction vessel, an inert gas is introduced into the reaction vessel, the temperature is raised to 370°C, and a mixed carbon source is added to react for 3.5 hours to obtain a first coating material. The mass ratio of ethanol, ethylene, benzene, hexachlorobenzene and ethylene in the mixed carbon source is 1:0.70.7:1.5:0.7. The ratio of the carbon content of the mixed carbon source to the carbon content of lithium iron phosphate in the active layer is 0.30:1. The D50 particle size of the lithium niobate powder is 6μm. The shell layer of the carbon and graphene coated particles consists of two layers, the first shell layer close to the core is a carbon layer, and the second shell layer is a graphene layer. The thickness of the first shell layer is 110nm, and the thickness of the second shell layer is 60nm. The first coating material is cooled, and when the temperature is lower than 200°C, the first coating material is transferred to a bag filter, and the second coating material is obtained by chemical vapor deposition.
[0069] The second coating material is ultrasonically dispersed in water to obtain a first dispersion, and the graphene is ultrasonically dispersed in water to obtain a second dispersion. The first dispersion and the second dispersion are mixed and uniformly dispersed by ultrasonic dispersion to obtain a mixed dispersion; the mixed dispersion is dried at 150°C and heat-treated at 200°C to obtain a second comparative carbon and graphene-coated particles. The total mass percentage content of the second comparative carbon and graphene-coated particles is 100 mol%, wherein the mass fraction of the first shell layer is 1.4%, the mass fraction of the second shell layer is 1%, and the mass fraction of the core is 97.6%.
[0070] Active layers are set on both sides of the positive electrode current collector to obtain a second comparative positive electrode sheet. The thickness of the first active layer is 44μm, and the thickness of the second active layer is 158μm. Specifically, the first active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, PVDF as the binder, and the above-mentioned second comparative carbon and graphene-coated particles as lithium supplements; and in the first active layer, the mass fraction of the positive electrode active material is 96.2%, the mass fraction of the conductive agent is 1.1%, the mass fraction of the binder is 2%, and the mass fraction of the lithium supplement is 0.7%. The second active layer of the positive electrode sheet uses lithium iron phosphate as the positive electrode active material, carbon black as the conductive agent, and PVDF as the binder; and in the second active layer, the mass fraction of the positive electrode active material is 96.6%, the mass fraction of the conductive agent is 1.2%, and the mass fraction of the binder is 2.2%. The D50 particle size of the lithium iron phosphate in the active layer is 1.7μm, and the powder compaction density is 2.0g / cm 3 , specific surface area 13m 2 The second comparative positive electrode sheet, negative electrode sheet, electrolyte and separator were assembled and packaged to obtain the second comparative secondary battery.
[0071] The first efficiency, internal resistance and energy retention rate of the first secondary battery, the second secondary battery, the third secondary battery, the fourth secondary battery, the fifth secondary battery, the sixth secondary battery, the first comparative secondary battery and the second comparative secondary battery were tested. Specifically, the test environment was adjusted to 25°C, the battery was charged to a voltage of 3.65V at a constant power of 0.5P, left to stand for 10 minutes, and then discharged to 2.5V at a constant power of 0.5P, left to stand for 10 minutes, and the charge and discharge cycle was 100 times.
[0072] The calculation formula for the first efficiency is: first efficiency = first discharge capacity / first charge capacity, internal resistance refers to the internal resistance measured by an ohmmeter after the first full charge, and energy retention rate = 100th cycle discharge energy / 1st cycle discharge energy × 100%. The experimental results are shown in Table 1.
[0073] The first secondary battery, the second secondary battery and the third secondary battery all have the first active layer and the second active layer on both sides of the positive electrode sheet. On the basis of the third secondary battery, the first active layer and the second active layer are only provided on one side of the positive electrode sheet to obtain the fourth secondary battery. On the basis of the third secondary battery, the content of carbon and graphene-coated particles in the first active layer is changed to obtain the fifth secondary battery and the sixth secondary battery.
[0074] Table 1 Battery energy retention rate experimental results First efficiency (%) Internal resistance (mΩ) Energy retention rate (25°C, 0.5P, 100 cycles, %) First secondary battery 94.67 0.21 99.2 Secondary battery 94.76 0.23 98.6 Third secondary battery 94.84 0.20 99.3 Fourth secondary battery 91.55 0.38 96.1 Fifth secondary battery 94.32 0.22 98.7 Sixth secondary battery 94.21 0.24 98.3 First comparison of secondary batteries 92.38 0.31 96.9 Second comparative secondary battery 92.31 0.32 96.6 The experimental results show that the secondary battery provided by the present application has high initial efficiency, low internal resistance, and high energy retention rate, so the cycle life of the secondary battery provided by the present application is longer. Specifically, when the content of carbon and graphene-coated particles in the first active layer is 0.9%, the cycle life of the secondary battery is longer; and compared with the secondary battery in which the active layer is arranged on one side of the positive electrode current collector, the cycle life of the secondary battery in which the active layer is arranged on both sides is longer.
[0075] The present application provides a secondary battery and a method for preparing the same. The secondary battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, the positive electrode comprises a current collector, an active layer is arranged on one or both sides of the current collector, the active layer comprises a first active layer and a second active layer, the first active layer is arranged between the second active layer and the current collector, the first active layer comprises carbon and graphene coated particles, the carbon and graphene coated particles are shell-core structures, the shell material is carbon and graphene, the core material is one of lithium ferrite, lithium nickelate and lithium niobate, the shell of the carbon and graphene coated particles is composed of two layers, the first shell close to the core is a carbon layer, and the second shell is a graphene layer. The cycle life is improved by changing the structure of the positive electrode sheet, and the problem of low cycle life of the secondary battery is solved. The present application also provides a method for preparing the above-mentioned secondary battery.
[0076] Similar parts between the embodiments provided in this application can be referenced to each other. The specific implementation methods provided above are only a few examples under the general concept of this application and do not constitute a limitation on the protection scope of this application. For those skilled in the art, any other implementation methods expanded based on the scheme of this application without creative work belong to the protection scope of this application.
Claims
1. A secondary battery, characterized in that: The secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet includes a current collector. An active layer is arranged on one side or both sides of the current collector. The active layer includes a first active layer and a second active layer. The first active layer is arranged between the second active layer and the current collector. The first active layer includes carbon and graphene coated particles. The carbon and graphene coated particles are a shell-core structure composed of an inner core and a shell layer surrounding the inner core. The material of the shell layer is carbon and graphene. The material of the inner core is one of lithium ferrite, lithium nickelate and lithium niobate. The shell layer is composed of a first shell layer close to the inner core and a second shell layer farther away from the inner core than the first shell layer. The first shell layer is a carbon layer, and the second shell layer is a graphene layer. The material forming the carbon layer includes a mixed carbon source, and the mixed carbon source includes ethanol, ethylene, benzene, hexachlorobenzene and ethylene.
2. The secondary battery according to claim 1, characterized in that: The mass fraction of carbon and graphene-coated particles in the first active layer is 0.8% to 1.0%.
3. The secondary battery according to claim 1, characterized in that: The D50 particle size of the core particles is 5 μm to 10 μm, the thickness of the first shell layer is 60 nm to 100 nm, and the thickness of the second shell layer is 70 nm to 120 nm.
4. The secondary battery according to claim 1, characterized in that: The active layer includes lithium iron phosphate, the D50 particle size of the lithium iron phosphate is 0.6 μm to 1.6 μm, and the powder compaction density is ≥ 2.3 g / cm 3 , specific surface area 8m 2 / g~12m 2 / g.
5. The secondary battery according to claim 1, characterized in that: The thickness of the first active layer is 40 μm to 50 μm, and the thickness of the second active layer is 140 μm to 160 μm.
6. A method for preparing a secondary battery, for preparing the secondary battery according to any one of claims 1 to 5, characterized in that: include: preparing carbon and graphene coated particles using carbon, graphene and core materials; sequentially coating the carbon and graphene-coated particles and lithium iron phosphate on one or both sides of a positive electrode current collector to obtain the positive electrode sheet; The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled and packaged to obtain the secondary battery.
7. The method according to claim 6, characterized in that Also includes: Inert gas is introduced into a reaction container containing the core material powder, and after heating, a mixed carbon source is added to obtain a first coating material; Cooling the first coating material and transferring it into a bag filter to obtain a second coating material; Ultrasonic dispersion of the second coating material in water to obtain a first dispersion, ultrasonic dispersion of graphene in water to obtain a second dispersion, and mixing the first dispersion and the second dispersion to obtain a mixed dispersion; The mixed dispersion is dried at 150° C. and heat-treated at 200° C. to obtain the carbon and graphene-coated particles.
8. The method according to claim 6, characterized in that Also includes: The core material powder is pre-treated and placed in a reaction container, an inert gas is introduced into the reaction container, the temperature is raised to 400°C to 800°C, a mixed carbon source is added and reacted for 0.2h to 3h to obtain a first coating material.
9. The method according to claim 6, characterized in that The ratio of the carbon content of the mixed carbon source to the carbon content of the lithium iron phosphate in the active layer is 0.32~0.35:1, the mixed carbon source includes ethanol, ethylene, benzene, hexachlorobenzene and ethylene, and the mass ratio of ethanol, ethylene, benzene, hexachlorobenzene and ethylene in the mixed carbon source is 1:0.8~1.2:0.8~1.2:0.8~1.2:0.8~1.
2.
10. The method according to claim 7, characterized in that Also includes: The first coating material is cooled down, and when the temperature is lower than 200° C., the first coating material is transferred into a bag filter, and the second coating material is obtained by chemical vapor deposition.
Citation Information
Patent Citations
Preparation method of in-situ graphene coated lithium ion battery cathode material
CN104934608A
Positive plate, lithium-ion battery positive lithium-supplementing material and preparation method of material
CN109786746A
Positive electrode sheet, preparation method thereof, lithium ion battery and vehicle
CN110729451A
Electrode additive, preparation method thereof and positive plate
CN114649529A
Li5FeO4 (at) rGO (at) C composite lithium supplement additive, preparation thereof and application of Li5FeO4 (at) rGO (at) C composite lithium supplement additive in lithium ion battery
CN115148961A
Cited By
Positive electrode sheet, battery, battery pack and electric device
WO2026158039A1
